PARTISIPASI DAN KEPUASAN PETANI TERHADAP KINERJA PENYULUH PERTANIAN DI KECAMATAN PALAS KABUPATEN LAMPUNG SELATAN - Indah Nurmayasari; Begem Viantimala; Dame Trully Gultom; Helvi Yanfika; Abdul Mutolib (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2020)
The success of extension activities is influenced by the participation of target farmers. In addition to participation, farmer satisfaction with extension performance will be related to extension of sustainability in the future. This study aims to analyze the participation and satisfaction of farmers on the performance of agricultural extension workers in Palas District, South Lampung Regency. The study was conducted in the extension work area of Palas Tang District which is an agricultural center, especially lowland rice in South Lampung Regency. The study was conducted from May to June 2019. Data collected in this study consisted of primary data and secondary data. Data analysis uses a Likert scale. The results of the study provide a picture that the participation of farmers in agricultural extension activities in the District of Palas is at a fairly high level. Make farmers active in farmer groups and propose extension activities by 56 percent, and farmer involvement in giving advice on the development of farmer groups with a percentage of 78 percent. All farmers join to become members of farmer groups without coercion from extension workers or other parties. In general, farmers' satisfaction with extension performance is quite satisfied. Of the nine indicators, farmers' satisfaction with mass movements in their work areas is the lowest. Farmers are satisfied with the way the agriculture instructor communicates. Farmers are satisfied with the way the instructor communicates and assesses extension activities as having a good impact on agricultural extension activities.